Rancang Bangun Sistem Informasi Penjualan dan Pembelian pada Toko Agnia Tanjungsari - Nugraha, Muhamad Fahmi; Fadilah, Rifa; Tryana, Anjas (Masoem University, 2023)
The use of computers as a tool for completing work in the field of information system technology is increasingly widespread and growing in all fields. Computers are felt to have many advantages, because computers can be programmed so that they can be adjusted to the wishes of the user. One way to get optimal results by managing data quickly and accurately is to use a computerized system and use system development, namely the Software Development Life Cycle (SDLC) with the Waterfall method in designing information systems, starting from analyzing software requirements, design, implementation, and Testing.Toko Agnia is currently still not optimal because sales and purchase data processing is carried out manually so it becomes ineffective. Based on the results of the reports that have been made, several conclusions can be drawn as follows: With the implementation of a desktop-based information system users will easily process sales, purchases and stock inventory, can speed up the processing and preparation of sales and purchases reports, the accuracy of calculations in this program can be relied upon.